Vitamin D3 Supplementation and Aquatic Exercise Combination as a Safe- Efficient Therapeutic Strategy to Ameliorate Interleukin-6 and 10, and Social Interaction in Children with Autism: Vitamin D and Exercise Combination in Children with Autism - AdibSaber, Fahimeh; Ansari, Soleyman; Elmieh, Alireza; Barkadehi, Babak (Iranian Journal of Child Neurology, 2024)
Objectives Increasing evidence demonstrated that there are altered levels of both pro-and anti-inflammatory cytokines in autism spectrum disorder (ASD) and pointed out that immune dysfunction may also relate to social deficits. This study aimed to investigate the effect of aquatic exercise combined with vitamin D supplementation on social interaction and two related cytokines (Interleukin-6 and Interleukin-10) in children with ASD. Materials & Methods Forty boys with ASD (mean age: 10.90; age range: 6–14 years) were randomly assigned to the three interventions (groups 1, 2, and 3) and one control group (each 10 participants). Participants in the group 1 and 3 received a 10-week aquatic exercise program. Subjects in groups 2 and 3 took orally 50,000 IU of vitamin D3/week. This study evaluated the serum levels of IL-6 and IL-10, as well as the participants’ social interaction at baseline and post-intervention. Results Compared to the control group, all three interventions improved social skills scores (p< 0.001). Surprisingly, the combination strategy could significantly reduce IL-6 and increase IL-10 serum levels in children with ASD. Conclusion Aqua-based exercise programs combined with vitamin D supplementation are recommended to benefit children with ASD and improve social and communication dysfunction